The Effect Of Compensation And Organizational Climate On Job Attitude Mediated By Nurse Motivation At Murni Teguh Sudirman Hospital, Jakarta - Erliana, Ria; Anindita, Rina; Mustikawati, Intan Silviana (Mutiara: Multidiciplinary Scientifict Journal, 2022)
Factors related to the quality of a hospital's service are the Job Attitude of health workers with a good nurse's Job Attitude, it can also create good health services for patients, where one of the dimensions of Job Attitude is job satisfaction. Employees who do not get job satisfaction will not achieve psychological satisfaction and eventually negative behavior arises. Conversely, employees who get job satisfaction will work well, enthusiastically, actively, thereby encouraging work passion and being able to perform better. Job Attitude/work attitude can be reflected in 4 indicators, namely leaving/exit, aspirations/voice, loyalty/loyalty, and neglect/neglect. Based on a report from the Human Resources (HR) unit for 2022, in the last 1 year there were 15 out of 66 nurses (± 23%) at Murni Teguh Sudirman Hospital Jakarta who resigned which according to Hasibuan (2012) the turnover should not be more than 10% . Even with the easing of the Covid-19 pandemic, the nurse turnover rate is getting higher. Researchers conducted a search, namely that more and more nurses felt that the compensation provided by the hospital was not in accordance with the workload given, the organizational climate was less supportive in professional development so that it had an impact on decreased work motivation.The purpose of this study was to analyze the effect of compensation and organizational climate on job attitudes mediated by the motivation of nurses at Murni Teguh Sudirman Hospital, Jakarta. This study uses a survey method, which is research that takes samples from a population using a questionnaire as the principal data collection tool to examine the observed symptoms or phenomena. This study uses a causality design based on the cross-sectional time dimension, namely measurements of the independent and dependent variables are carried out at the same time. The unit of analysis is the individual, the data analysis method uses Regression. The number of samples obtained and fulfilling the inclusion criteria was 55 samples. Based on the research results, it was found that compensation, organizational climate and motivation simultaneously had an influence on job attitude, but motivation could not be an intervening variable. The implications of this research in theory will prove the influence of research variables and managerially can improve the compensation system in hospitals.